Self-Efficacy of Physical Education Student Interns in to Engage their Pupils after Training in Body Language and Public Speaking (Global Journal of Human-Social Science, 2021)
This research aims to develop and test a training device in 'Body language and public speaking' centered on the development and consolidation of communication skills in future teachers of physical education in Tunisia. The effectiveness of the device was evaluated based on the evolution of the feeling of self-efficacy of the student interns to keep their pupîl's engaged in learning situations before and after a specific training of "Body language and public speaking" throughout the work-life preparation course. To make this study a reality, we involved two groups of student interns. A first group to assume the role of witness received ordinary initial training provided by the 'Higher Institute of Sport and Physical Education (Ksar Saïd)'. A second group to assume the experimental role received the same initial training but was also involved in the training device designed for this study. The change in the feeling of self-efficacy was measured using the French version of the Ohio State Teacher Efficacy Scale (OSTES) questionnaire recognized in the literature (Ménard, L., Legault, F. & Dion, J-S., 2012) as an instrument measuring the effectiveness of the teacher with regard to student engagement as the main indicator of classroom management.
Keywords: communication skills; 'body language and public speaking’; student interns